Mucormycosis in a Patient with Uncontrolled Diabetes Mellitus - Mehmet Turan İnal; Dilek Memiş; Pervin Hancı; Gökhan Günbay; Samet Keleş; Habibe Tülin Elmaslar Mert; Rüveyde Garip; Selis Gülseven Güven; Emre Hocaoğlu; Banu Tütüncüler (Galenos Yayinevi, 2022)
Mucormycosis; is a rapidly progressive fungal infection due to filamentous fungi of the mucoraceae family. In this case report, we aimed to present the diagnosis and treatment modalities of a patient who developed rhinoorbital mucormycosis. A 54-year-old patient with a history of hypertension applied to the emergency department with a complaint of wound in the mouth that started four days ago. In the examinations performed here, the patient was diagnosed with diabetic ketoacidosis. In the examination of the patient, it was found that there was a necrotic wound on the left hard palate, a necrotic wound extending from the left inferior turbinate to the nasopharynx, and hyphae in the nasal passage. The patient underwent an aggressive debridement operation on the third day, due to the growth in the fungal culture. In the following clinical examination of the patient, ketone in the urine became negative, and his acidosis status improved. On the same day, the patient was treated with a positive coronavirus disease-2019 (COVID-19) polymerase chain reaction. After 15 days of treatment, the patient died due to COVID-19 pneumonia. Mucormycosis should be doubtful in patients presenting with uncontrolled diabetes mellitus and severe sino-orbital infection. All physicians following diabetic ketoacidosis should be vigilant against this rapidly progressing disease with high mortality.